Electron microscopic studies on the attachment of Mycoplasma pneumoniae to guinea pig erythrocytes. - Brunner, H (1979)
A mechanism of pathogenicity of Mycoplasma pneumoniae is its ability to attach to the surface of mammalian cells. It has previously been demonstrated by others that M. pneumoniae adheres with a specialized terminal structure, the "tip," to ciliated epithelial cells of the respiratory tract. In this report we show by electron microscopy that M. pneumoniae adsorbs with membrane sites other than the tip to guinea pig erythrocytes.